Thyroid sonography as an extension of the bedside examination in hyperthyroidism - Kyriacou, Angelos; Economides, Panayiotis A; Syed, Akheel A (Journal of Medical Science, 2020)
In this mini-review, we discuss the role of thyroid sonography as a ‘point-of-care’ tool for assessing and managing patients with (suspected) hyperthyroidism who present to the endocrine outpatient clinic. A thyroid ultrasound may aid in distinguishing between hyperthyroidism and destructive thyroiditis. The presence of intense vascularity (‘thyroid inferno’) on the power Doppler has a very high positive predictive value in identifying hyperthyroidism. It may also allow for the sub-classification of hyperthyroidism into autoimmune and nodular hyperthyroidism. It is important to identify the presence of thyroid nodules at an early stage, as this may influence management. Toxic nodules requires definitive treatment, as well as the presence of nodules in Graves’ disease because of increased risk of malignancy. Current guidelines on hyperthyroidism do not clearly state thyroid sonography as a first line investigation, although recent authoritative reviews point in that direction. Given the aforementioned benefits of thyroid sonography, alongside the reduced costs and widespread availability of high-resolution (including portable) ultrasound devices, there is an argument for thyroid sonography to be applied as a first line investigation for all patients with hyperthyroidism. Endocrinologists trained in thyroid sonography could perform this as an extension of their clinical examination when patients first present with hyperthyroidism at the endocrine clinic.